STUDI KARAKTERISASI MIGRASI FOSFAT LUMPUR IPAL YOGYAKARTA DALAM TANAH MENGGUNAKAN PERUNUT 32P - Muharini, Anung; Wijayanti, ester; Ardiani, Donna (Jurnal Teknologi Lingkungan, 2001)
IPAL Yogyakarta mud contains high concentration of phosphate that can polute groundwater. To study phosphate migration with matematical model needs the data of soil properties and phosphate migration characterization in that soil. The phosphate migration characterization is determine in laboratorium scale using soil colomn nethod. The soil that are used in this research are soil at IPAL location (IPAL soil) and soil at soil at Physics Engineering Department GMU (PE soil). The tracer that is used is 32P radioisotop dan the detector is Geiger Muller detector. For IPAL soil the soil mass is 20 g, soil length is 2,1 cm, water height is 20 cm, and the flow rate of water 0,0038 cm3/s. For PE soil the soil mass is 25 g, soil length is 2,2cm, water height is 20 cm, and the flow rate of water are 0,0275 cm3/s and 0,0071 cm3/s.The result shows that IPAL soil is clay class soil and PE soil is sand class soil. The IPAL soil porosity is 0,2997 and PE soil is 0,303. IPAL soil permeability is 5,6984x10-5 cm/s and the average velosity is 1,79x10-4 cm/s. On PE soil for the flow rate of 0,0275 cm3/s the soil permeability is 4,338x10-4 cm/s, average velocity is 1,2818x10-2 cm/s, distribution coefficien is 0,88 ml/g, dispertion coefficien is 8,0971x10-3 cm2/s, phosphate migration velocity is 3,6429x10-3 cm/s, and the retardation factor is 3,5186. For the flow rate of 0,0071 cm3/s the soil permeability is 1,110x10-4 cm/s, average velocity is 3,322x10-3 cm/s, distribution coefficien is 1,345 ml/g, dispertion coefficien is 2,5339x10-3 cm2/s, phosphate migration velocity is 9,8888x10-4 cm/s, and the retardation factor is 3,3594. For the higher of flow rate the migration is higher. IPAL soil has capability to hold polutans.